2018
DOI: 10.21037/jtd.2018.09.144
|View full text |Cite
|
Sign up to set email alerts
|

A review and analysis of strategies for prediction, prevention and management of post-operative atrial fibrillation after non-cardiac thoracic surgery

Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia after non-cardiac thoracic surgery and is associated with a significant increase in perioperative morbidity, intensive care unit (ICU) admission, and mortality. Practical guidance is needed to assist clinicians in managing this critical issue and direct further research. Here we aim to provide a synoptic review and analysis of the literature to distil practical recommendations for prediction, prevention and management of post-operative atrial fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The role of both the LA and ventricle in the development of AF has been extensively demonstrated. [14][15][16] While LAVi was reported to have better predictive value than LVGLS in the estimation of POAF development in one study, another study reported that lower preoperative LVGLS could be associated with POAF. 17,18 Although the involvement of LA volume and functions is well known in the development of POAF, [19][20][21] Finally, AF with rapid ventricular response may also cause myocardial ischemia and tachycardiomyopaty.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The role of both the LA and ventricle in the development of AF has been extensively demonstrated. [14][15][16] While LAVi was reported to have better predictive value than LVGLS in the estimation of POAF development in one study, another study reported that lower preoperative LVGLS could be associated with POAF. 17,18 Although the involvement of LA volume and functions is well known in the development of POAF, [19][20][21] Finally, AF with rapid ventricular response may also cause myocardial ischemia and tachycardiomyopaty.…”
Section: Resultsmentioning
confidence: 98%
“…In our study, LAVi, LVGL, and sPAP were closely associated with POAF development, which is consistent with the literature data. The role of both the LA and ventricle in the development of AF has been extensively demonstrated . While LAVi was reported to have better predictive value than LVGLS in the estimation of POAF development in one study, another study reported that lower preoperative LVGLS could be associated with POAF .…”
Section: Discussionmentioning
confidence: 99%
“…IV amiodarone has multiple indications that can be used in a variety of settings, with its primary use to treat patients who are hemodynamically unstable with atrial or ventricular arrhythmias (Hilleman, & Spinler, 2012). In addition, it can be used to prevent atrial fibrillation post‐thoracic surgery (Smith et al, 2018; Zhao et al, 2017). Approximately 12%–46% of patients are at risk for atrial fibrillation after thoracic surgery, the most common complication (Smith et al, 2018; Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 12%–46% of patients are at risk for atrial fibrillation after thoracic surgery, the most common complication (Smith et al, 2018; Zhao et al, 2017). Patients may experience palpitations, dizziness, chest pain, shortness of breath, or hypotension when untreated, which can lead to increased morbidity, risk for ischemic stroke, longer length of stay, and the need for escalation of care (Rienstra et al, 2012; Smith et al, 2018; Zhao et al, 2017). Male patients with advanced age, an oncologic history, and comorbid conditions of the lungs are at increased risk compared to the general population (Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation